Fc receptor-like 5 gene polymorphisms and mRNA expression are associated with liver fibrosis in chronic hepatitis B - Yang, Jiajia; Gu, Juan; Wang, Hongmei; Shi, Jiayin; Lu, Lingyun; She, Wanxian; Wang, Ying (Frontiers in Microbiology, 2022)
Objective: To investigate the associations of Fc receptor-like 5 (FCRL5) gene polymorphisms and mRNA expression with liver fibrosis in chronic hepatitis B (CHB). Methods: A total of 114 CHB patients with liver fibrosis and 120 CHB patients without liver fibrosis were selected for this study. The gender, age, body mass index (BMI), alanine transaminase (ALT) value, aspartate aminotransferase (AST) value, aspartate aminotransferase-to-platelet ratio index (APRI), and fibrosis index based on 4 factors (FIB-4) were recorded. Two polymorphisms of the FCRL5 gene (rs6427384 and rs6692977) were genotyped. The mRNA expression level of FCRL5 in peripheral blood monocytes was determined. Results: ALT, AST, APRI, and FIB-4 in patients with fibrosis were significantly higher than those in non-fibrosis patients. There was statistically significant difference between fibrosis and non-fibrosis groups in the genotype distribution (χ2 = 7.805, p = 0.020) and allele frequencies (χ2 = 13.252, p < 0.001) at FCRL5 rs6692977. When compared with CC genotype, the genotype CT or TT at rs6692977 was significantly associated with a increased risk of liver fibrosis in CHB patients (CT vs. CC: OR = 1.921, 95% CI = 1.093–3.375, p = 0.023; TT vs. CC: OR = 2.598, 95% CI = 1.067–6.324, p = 0.031). The mRNA relative expression levels of FCRL5 in patients with liver fibrosis were significantly higher than those in the non-fibrosis group (t = 13.456, p < 0.001). The fibrosis patients carried TT or CT genotype of rs6692977 had significantly higher FCRL5 mRNA expression levels than those carried CC genotype (t = 2.859, p = 0.005). The mRNA expression levels of FCRL5, APRI, and FIB-4 index showed predictive efficacy in liver fibrosis with cut-off values of 0.75 (AUC = 0.896, 95% CI = 0.856–0.935), 0.45 (AUC = 0.852, 95% CI = 0.802–0.902) and 1.84 (AUC = 0.765, 95% CI = 0.703–0.826), respectively. Conclusion: FCRL5 gene rs6692977 polymorphisms and mRNA expression levels are associated with liver fibrosis in CHB patients.